Diversity and genetic parameter of chili pepper (Capsicum annuum) based on yield component in three location - Tri Wahono Dyah Ayu Sayekti; MUHAMAD SYUKUR; SRI HENDRASTUTI HIDAYAT; AWANG MAHARIJAYA (Society for Indonesian Biodiversity, 2021)
Abstract. Sayekti TWDA, Syukur M, Hidayat SH, Maharijaya A. 2021. Diversity and genetic parameter of chili pepper (Capsicum annuum) based on yield component in three locations. Biodiversitas 22: 823-829. With the increase in the use of chili, it is necessary to develop these commodities through plant breeding activities. Phenotypes are not only determined by genetics, but also by environmental factors and the GxE interactions, so all the factors need to be considered. The aims of this study were to evaluate the variability of ten elite breeding lines and three commercial varieties of chili pepper (Capsicum annuum L.) across three different environments. This experiment was conducted in three environments namely Bogor, Kolaka, and Palembang, from January until July 2019. Thirteen genotypes consisting of ten elite lines and three commercial chili pepper were used. This experiment was arranged in a randomized complete block design (RCBD) with three replications for each environment. To determine the effect of environment, Combined Analysis of Variance was carried out for all environments using PBSTAT-GE. The environment used in this experiment was lowland that varies between each other. The genotype with the fastest harvesting age relative in three environments was F7-145293-19-8-3-113-1. The highest number of fruits per plant was observed in genotype F9-160291-9-4-3-2-1-1-1 with 261 fruits per plant. The highest yield was observed in genotype F7-145174-9-7-1-5-3. From the clustering analysis, this population was grouped into five clusters. The heritability values for the 12 observed traits ranged between 22.68-69.97%, classified into high and moderate criteria.